Research of Working Characteristics of Alternative Motor Fuels in Their Combustion - M. S. Assad (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2007)
Air-fuel mixtures of various composition, using hydrogen, have been investigated in the paper. The paper shows dependences of the investigated mixtures’ combustion duration on an initial pressure and a coefficient of oxidizer (air) excess. While adding hydrogen an analysis of mixture burning speed influence on the combustion process in the modeling chamber of internal combustion engine has been carried in the paper. The paper reveals combustion peculiarities while applying hydrogen in the area of poor mixtures.